2013
DOI: 10.2478/s11535-013-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

Galleria mellonella infected with Bacillus thuringiensis involves Hsp90

Abstract: Insects are good models for studying the innate immune response. We report that Galleria mellonella larvae infected with entomopathogenic bacteria Bacillus thuringiensis kurstaki show changes in the level of Hsp90. Our experimental approach was to pre-treat larvae with the Hsp90-binding compound, 17-DMAG, before infection with B. thuringiensis. We show that pre-treated animals display a higher level of immune response. This was mainly manifested by enhanced action of their hemolymph directed toward living bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Reciprocally, in other invertebrate models, infection appears to enhance temperature stress tolerance, stress responses, and expression of stress genes, including HSR target genes. Bacterial infection induced Hsp90 expression in the greater wax moth 72 and Hsp70 expression in Musca domestica 73 . Hormesis, the beneficial effects of a treatment that are harmful at a higher intensity 74 , may be the underlying mechanism in these other invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocally, in other invertebrate models, infection appears to enhance temperature stress tolerance, stress responses, and expression of stress genes, including HSR target genes. Bacterial infection induced Hsp90 expression in the greater wax moth 72 and Hsp70 expression in Musca domestica 73 . Hormesis, the beneficial effects of a treatment that are harmful at a higher intensity 74 , may be the underlying mechanism in these other invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the heat shock proteins present in various insect species by Zhao and Jones found the most common forms to be HSP90 and HSP70; however, HSPs were identified in a range of insects from the orders Lepidoptera, Diptera, Hymenoptera, Psocoptera and Hemiptera [43]. One of the few published articles that discuss the presence of HSP in G. mellonella, by Wojda et al, indicates that injection of entomopathogenic Bacillus thuringiensis cells causes HSP90 levels in larval fat bodies to increase approximately two-fold 1.5 hours after infection, and this rise is followed by a fall to slightly below control levels three hours after infection [44].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the antibacterial response, it was shown that HSP70 transcripts were highly induced in arthropods ( Penaeus monodon ) after injection with bacteria Vibrio [ 82 ]. In wax moths, an increase in HSP90 expression was observed in response to Bacillus thuringiensis infection [ 83 ] and mixed (bacteria and yeast) infections [ 84 ]. Linder and coworkers [ 16 ] suggest that HSPs may improve immune functions against bacterioses at cool temperatures in Drosophila melanogaster .…”
Section: Discussionmentioning
confidence: 99%